Análise econômica da implantação de um sistema fotovoltaico conectado à rede em uma indústria - TEIXEIRA, Vanessa Nogueira (2022)
The energy generated by the sun through the photovoltaic system is characterized by being an attractive alternative for generating electricity, since it is a natural resource available that being properly handled can provide benefits such as decreased spending on power generation and preservation environment. Brazil has the potential to be one of the largest producers and consumers in this sector with a view that is one of the world's largest silicon producers and has high solar incidence. As a result, this paper presents a feasibility study of electricity generation through photovoltaic system connected to the network in the industrial sector realized from the actual data collection and site characteristics where you want to install the system and electric power bills because from this information you can set the system power, design, budget, and finally perform the calculations regarding the economic analysis to demonstrate whether it is more feasible to use the power supplied by the local utility or generated by the photovoltaic system.